THE EFFECT OF DUAL ROLE WOMAN PERFORMANCE AS A CIVIL SERVANT IN THE LEVEL OF GOVERNMENT TOMOHON - Mait, Swingli; Mekel, Peggy Adeline (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Today, woman in Indonesia their role as a housewife has been divided with role as an employee to meet the family needs because of unfavorable economic conditions. However having to simultaneously act for two roles is not easy. This situation will result in a very significant achievement for business establishments, which is affected their performance in the office. This study aimed to determine the influence of role as a housewife and role as an employee to the employee performance as a civil servant in the level of government Tomohon. This research used quantitative method. The analytical method used was multiple linear regression analysis. The data used in this research is primary data obtain through the questionnaire. The population observed is the married woman in the level of government Tomohon with sample as many as 100 respondents. Result of the analysis showed that both role as a housewife and role as an employee has a significant influence to the Employee Performance as a civil servant in the level of government Tomohon. The Tomohon city government’s still consider the dual role of career woman and still maintain the performance of employees especially career women who have a family in order to keep balance between their work in the office with their obligations at home as a housewife, and with regard to their discipline in work. Keywords: role as a housewife, role as an employee, employee performance